An approach to data collection in compassionate use/managed access - Sarp, Séverine; Reichenbach, Ramona; Aliu, Paul (Frontiers in Pharmacology, 2022)
Compassionate Use (CU)/Managed Access programs provide access to locally unapproved medicines. As these programs become more global and involve a broader range of products, determining whether patients derive benefit from treatment could provide insights into therapeutic use in a real-word setting with diverse pools of patients. CU primary purpose is to provide treatment and it is not targeting research. However, it is increasingly considered as a source of real-world data. In the absence of a harmonized framework on CU data collection, Novartis developed a company-wide guidance to collect baseline patient data and prospective follow-up information at product resupply. Although this approach has recently been implemented and utilization of this data has been mainly internal to the company so far, the prospective collection of key efficacy parameters in patients receiving therapies via CU could potentially be used as a supportive set of information collected in a real-world setting to be submitted in addition to clinical trial data, if not as a main source of data for regulatory submission.